Analisis Ekuitas Merek Pasta Gigi Pepsodent - Susanta Susanta (Jurnal Paradigma, 2009)
Numbers of toothpaste tighten competition. In order to winner in competition market, corporate must be able to develop a good perception in the point of view consumers. Corporate must convince its consumers that its products best for buy. Managing product perception can be done through developing brand loyally. Brand is name, term, sign, design symbol, or its combination in which products ident!fied by consumers. Identification function is to dfferenti ate a corporate produced from competitor A prestigious brand is a brand, which has strong brand equity. Brand equity is a batch brand asset and liabilities connected with one ‘s brand, name, symbol, which able increase or decrease product value for both corporate and consumers. Aim of this research is describe Pepsodent’s brand equity. Questioner used to collect data from 67 representative respondents. Result of this research show that Pepsodent brand awareness stand on the higher rank Pepsodent associated with; cheap, have a balance content, simple to uses, complete, cause fresh breath, make tooth healthy, reduce plaque, reinforce tooth, easy be sought, customer service available. Commonly consumer perception to Pepsodent is poorly. Commit buyer only 6% from total respondents. Corporate need to stimulate liking consumers in order to be commit buyer. Corporate need improve product quality against in consumer expectancy growing. Key word: Brand equity, top of mind, brand association, perceived quality, brand loyally.